Ex situ conservation of plant genetic resources in Russia: history, current status and perspectives - Gavrilenko, Tatjana (MTT, 2008)
The N.I. Vavilov Institute of Plant Industry (VIR) is the only research institution in Russia whose activities and responsibilities include the collecting of plant material from its source populations, maintenance and conservation of plant genetic resources. The VIR and its history are widely known. In 1920th outstanding Russian plant scientist Nikolay Vavilov was elected as Director of VIR. Nikolai Vavilov first called attention to the importance of collecting, storing and utilization of exotic germplasm for increasing agricultural production and providing humankind with more food. To this time the origin of conservation of plant genetic resources can be traced. Since 1920th Nikolai Vavilov and his colleagues visited 65 countries where they systematically collected plant germplasm of crop species and their wild relatives to accumulate and store plant genetic resources ex situ at VIR. Over the 100 years of it s history, VIR has organized 1,550 expeditions (both international and domestic) to all continents in all of the climatic zones. The VIR collecting missions and collection s evaluation are based on the Vavilov's concepts: 1. The theory of centres of origin of cultivated plants. 2. The law of homologous series in variation. 3. Vavilov s differential method and approach to study ecogeographical diversity. At present VIR holds one of the biggest and oldest plant germplasm collections worldwide. Its collection represents plant diversity of crop species and their wild relatives encompassing 323,000 accessions of 64 botanical families, of 376 genera, of 2,169 species including bred varieties, landraces, mutants and wild populations. Plant germplasm collections of VIR are maintained at the experimental stations in different regions of Russia. The germplasm collections are catalogued and characterized. The web-based database (www.vir.nw.ru) provides passport data for VIR collection. The main objectives of VIR are to collect, maintain, document, characterize, evaluate, conserve, regenerate plant germplasm and distribute of seeds and clonal stocks. Much of the material is phenotyped. Inter- and intraspecific diversity of plants is evaluated for resistance to biotic and abiotic stresses and for quality traits. Current stocks of VIR gene bank include seed base collections, field-grown plants of vegetatively propagated species, in vitro base collections, cryopreserved material, DNA extracts. VIR provides long-term conservation of seed collections which are stored in sealed glass bottles or in foil packets and kept at -10ºC and +4ºC in a chambers. Plant seed accessions are divided into: basic (25,000 accessions) and active (more than 200,000 accessions) collections. Long-term storage of seeds at low temperature is the most convenient, traditional method for plant germplasm conservation. However, this method is not applicable for vegetatively propagated species. The collections of vegetatively propagated species consist of small berries, fruit crops and grapevine, including about 23,000 accessions, and a potato collection including about 9,000 accessions. Most germplasm of the vegetatively propagated crops at VIR is maintained in field collections. However, these collections are endangered by diseases, pests and abiotic stress. To avoid the possible loss of these germplasm collections, new strategies, technologies and information are developed. Currently about 700 stocks of clonally propagated germplasm are stored under in vitro conditions, among them about 300 accessions of berries and fruit crops (raspberries, blackberries, strawberries, cherries, plums, currant, blue honeysuckle) and about 300 stocks of potato. Program of preservation of clonally propagated crops under in vitro conditions includes: testing and eliminating of viral and bacterial diseases, establishing in vitro culture, micropropagation, virus indexing, medium-term in vitro preservation and genotyping. DNA (RAPD and SSR) and isoenzyme markers have been applied to establish a database for cultivar genotyping of potatoes, raspberries and blackberries. Cryogenic facilities have been recently installed at VIR and they are available for developing cryopreservation. At present there are pollen cryocollections (samples of 198 accessions of wild species of some fruit and small berry crops) and cryopreserved winter buds of about 80 accessions of apple). Cryopreservation of in vitro meristem of potato has been recently applied. Long-term conservation of biodiversity of vegetatively propagated plants needs further developing of the theoretical and methodical approaches of in vitro and cryopreservation. This requires greater scientific co-operation in developing and standardizing techniques and methods.
Keywords: Ka; varieties; landraces; mutants; wild populations; seeds; clonal stocks; in vitro base collections; cryopreserved material; DNA extracts